Preparation and application of graphene composite carbon nanotube coated Co nanoparticle wave-absorbing material
The carbon nanotubes coated with Co nanoparticles were prepared by self-assembly method, and the crosslinked structure was formed with graphene oxide by hydrothermal method, which solved the shortcomings of existing carbon-based materials in terms of magnetic and impedance matching, and achieved the efficient electromagnetic wave absorption performance of graphene composite carbon nanotube coated with Co nanoparticle absorbing materials.
Patent Information
- Application Number
- CN202411892140.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
Existing carbon-based materials such as graphene oxide and carbon nanotubes have shortcomings in magnetic and impedance matching and cannot meet the requirements of modern absorbing materials.
Carbon nanotubes coated with Co nanoparticles were prepared by self-assembly method, and cross-linked structures were formed with graphene oxide by hydrothermal method to prepare graphene composite carbon nanotube coated with Co nanoparticle wave absorbing material.
The material's efficient electromagnetic wave absorption performance is achieved, which is specifically manifested as the maximum reflection loss at 8.03GHz is as high as -71.17dB, the effective absorption bandwidth is 3.02GHz, and has good wave absorption performance.
Smart Images

Figure CN119709123A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wave absorbing materials, and in particular relates to the preparation and application of graphene composite carbon nanotube coated Co wave absorbing materials. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the rapid development of the electronics industry, the safety issues brought by electromagnetic radiation have become increasingly prominent, and electromagnetic pollution has become the fourth largest pollution after air pollution, water pollution, and noise pollution. The emergence of absorbing materials can effectively protect against electromagnetic radiation, so high-efficiency absorbing materials have also become a hot topic in research.
[0004] Carbon-based materials have attracted attention due to their advantages such as light weight and strong dielectric loss absorption performance, especially graphene oxide (GO) and carbon nanotubes. GO has a unique two-dimensional honeycomb structure and electromagnetic wave action mechanism. The many defects and functional groups inside it can enhance the material's interface polarization and dipole polarization capabilities, which is conducive to the absorption of electromagnetic waves. Carbon nanotubes have a small diameter, high aspect ratio, high conductivity and mechanical strength. In addition, GO with a large specific surface area and carbon nanotubes with a porous structure provide the possibility of preparing low-density materials with high strength and toughness. The above characteristics provide a new direction for the development of composite materials with high-efficiency wave absorption performance. However, GO and carbon nanotubes have poor magnetic and impedance matching and cannot meet the requirements of modern wave absorbing materials. Therefore, it is urgent to develop a GO / carbon nanotube composite material with high-efficiency electromagnetic wave absorption performance. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first aspect of the present invention provides a graphene composite carbon nanotube-coated Co nanoparticle absorbing material with excellent absorbing performance, which is obtained by cross-linking graphene with carbon nanotubes, and the carbon nanotubes are loaded with Co nanoparticles.
[0006] Preferably, the X-ray crystal diffraction result of the absorbing material has a 2θ diffraction angle including a characteristic peak of graphene 2θ=26.5°, and characteristic peaks of Co nanoparticles 44.6°, 51.5° and 75.8°.
[0007] Preferably, the diameter distribution of the carbon nanotubes is 40-50 nm.
[0008] The preferred particle size of the Co nanoparticles is 40 to 50 nm.
[0009] Preferably, the preparation method comprises the following steps:
[0010] S1, preparing a melamine precursor by a self-assembly method using melamine, cobalt salt and ethanol, and preparing carbon nanotubes coated with Co nanoparticles by calcining in an inert gas;
[0011] S2. The carbon nanotubes coated with Co nanoparticles and graphene oxide are hydrothermally prepared into a graphene composite carbon nanotube-coated Co nanoparticle absorbing material.
[0012] Preferably, in step S1, the cobalt salt is cobalt nitrate hexahydrate.
[0013] Preferably, the mass ratio of melamine, cobalt salt and ethanol is 1:1:20-25.
[0014] In the above scheme, the nitrate of the cobalt salt and melamine form a self-assembly through electrostatic action and hydrogen bonding, and the cobalt ions are adsorbed in the self-assembly. Ethanol is added to the system, and the ethanol and the self-assembly are uniformly mixed. During the roasting process, the ethanol can be used as a carbon source to generate carbon nanotubes through roasting, and can also be used as a reducing agent to reduce the cobalt ions adsorbed in the self-assembly to form cobalt nanoparticles, thereby obtaining carbon nanotubes coated with Co nanoparticles. By controlling the mass ratio of melamine, cobalt salt and ethanol, the relative mass of cobalt nanoparticles and carbon nanotubes in the carbon nanotubes coated with Co nanoparticles can be controlled. In addition, the roasting temperature, time and heating rate have an important influence on the size of cobalt nanoparticles and carbon nanotubes, thereby affecting the performance of the final absorbing material.
[0015] Preferably, the graphene oxide is prepared by NaNO3, KMnO4 and hydrogen peroxide.
[0016] In the above scheme, the classic Hummers method is used to prepare graphene oxide. This method has high safety and can obtain GO rich in oxygen-containing functional groups, which has good dispersibility in aqueous solution. By adjusting the ratio of strong oxidant and GO, and controlling the extension of reaction time or increasing the reaction temperature, the type of oxygen-containing functional groups on the GO surface can be adjusted.
[0017] Preferably, in step S2, the mass ratio of carbon nanotubes coating Co nanoparticles to graphene oxide is 1:10-20.
[0018] Preferably, in step S2, the hydrothermal method temperature is 100-120° C., and the reaction time is 1-3 h.
[0019] In this scheme, carbon nanotubes coated with Co nanoparticles and graphene oxide containing rich oxygen-containing functional groups are reacted by hydrothermal method, and carbon nanotubes and graphene oxide form a cross-linked structure to improve the stability of the material. By adjusting the ratio of carbon nanotubes coated with Co nanoparticles and graphene oxide, the wave absorption ability of the material can be regulated.
[0020] On the other hand, the present application also includes the application of the above-mentioned graphene composite carbon nanotube-coated Co absorbing material in the field of electromagnetic wave absorption.
[0021] The present invention has the following beneficial effects:
[0022] 1. In the preparation process of carbon nanotubes coated with Co nanoparticles in the present invention, nitrate ions and melamine are used to form self-assembly bodies through electrostatic action and hydrogen bonding under acidic conditions, and cobalt ions are adsorbed in the self-assembly bodies. This pre-assembled precursor is conducive to the orderly arrangement and assembly of materials during high-temperature roasting, thereby achieving controllable synthesis process. Ethanol in the system serves as both a carbon source and a reducing agent, reducing cobalt ions to cobalt nanoparticles during roasting, thereby improving the purity and stability of cobalt doping in the absorbing material.
[0023] 2. On the basis of the above, graphene oxide was prepared by the classic Hummers method, and graphene composite carbon nanotube-coated Co nanoparticle absorbing material was prepared by the hydrothermal method. The entire preparation process is simple, the reaction conditions are mild, and it has prospects for industrial application.
[0024] 3. When the thickness of the absorbing material of the present invention is 3.3 mm, the maximum reflection loss at 8.03 GHz is as high as -71.17 dB, and the effective absorption bandwidth is 3.02 GHz, which has good absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention provides a scanning electron microscope (SEM) and transmission electron microscope (TEM) image of the graphene composite carbon nanotube-coated Co nanoparticle absorbing material prepared by the present invention, wherein Figure (a) is the SEM image of Example 1, Figure (b) is the SEM image of Example 2, Figure (c) is the SEM image of Example 3, Figures (d), (e) and (f) are TEM images of Example 2 at different fields of view, and Figures (g), (h), (i) and (j) are the corresponding C, N and Co element mapping spectra of Figure (f).
[0026] Figure 2 It is the XRD spectrum of the graphene composite carbon nanotube-coated Co nanoparticle absorbing material prepared by the present invention.
[0027] Figure 3 The hysteresis loops of different graphene composite carbon nanotube-coated Co nanoparticle absorbing materials (a) and the enlarged curves around the origin (b).
[0028] Figure 4These are normalized impedance matching diagrams of different graphene composite carbon nanotube-coated Co nanoparticle absorbing materials, wherein Figure (a) is the material of Example 1, Figure (b) is the material of Co Example 2, and Figure (c) is the material of Example 3.
[0029] Figure 5 These are reflection loss diagrams of different graphene composite carbon nanotube-coated Co nanoparticle absorbing materials, wherein Figures (a), (b), and (c) are two-dimensional reflection loss diagrams; Figures (b), (d), and (f) are three-dimensional reflection loss diagrams; (a) and (b) correspond to Example 1, Figures (c) and (d) correspond to Example 2, and Figures (e) and (f) correspond to Example 3. DETAILED DESCRIPTION
[0030] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The technical scheme of the present invention is further described below in conjunction with embodiments. The following embodiments are only used to illustrate the present invention, but are not intended to limit the scope of the present invention in any form.
[0032] Example 1
[0033] A method for preparing a graphene composite carbon nanotube-coated Co nanoparticle absorbing material specifically comprises the following steps:
[0034] S1. Preparation of carbon nanotubes coated with Co nanoparticles (abbreviated as Co@NCNTs, the same below) by self-assembly method: Melamine (2g) and Co(NO3)2·6H2O (2g) were added to a 100mL beaker containing 60mL of alcohol, ultrasonically stirred for 60min, and then dried at 60℃ in a vacuum drying oven for 36h. The obtained powder was placed in a quartz tube, and the quartz tube was heated to 800℃ at a rate of 4℃ / min in a mixture of hydrogen and argon, and maintained for 2h. The obtained product was named Co@NCNTs.
[0035] S2. Preparation of GO by Hummers method: Add 2g graphite and 1g NaNO3 into a 500ml beaker and stir evenly. Add 1ml concentrated H2SO4 in an ice-water bath and stir for 15min. Then add 6g KMnO4 and continue stirring for 15 minutes. Transfer the mixture to a 45℃ constant temperature water bath and stir for 3h. Slowly add distilled water to the obtained brown solution and continue stirring at 95℃ for 15min. After cooling, add 50ml deionized water and then add 2ml of 30% hydrogen peroxide solution.
[0036] S3. Preparation of Co@NCNTs / GO by hydrothermal method: Co@NCNTs (100 mg) was added to the final solution prepared in S2, and ultrasonic stirring was performed for 5 h. The resulting solution was then transferred to a hydrothermal autoclave lined with tetrafluoroethylene and maintained at 110°C for 2 h to obtain a graphene composite carbon nanotube-coated Co nanoparticle absorbing material, named Co@NCNTs / GO-1.
[0037] Example 2
[0038] This embodiment provides a method for preparing a graphene composite carbon nanotube-coated Co nanoparticle absorbing material, which specifically includes the following steps:
[0039] The amount of Co@NCNTs in step (4) of Example 1 was changed to 150 mg, and the other steps and the amounts of reactants were exactly the same as in Example 1 to obtain a graphene composite carbon nanotube-coated Co nanoparticle absorbing material, named Co@NCNTs / GO-2.
[0040] Example 3
[0041] This embodiment provides a method for preparing a graphene composite carbon nanotube-coated Co nanoparticle absorbing material, which specifically includes the following steps:
[0042] The amount of Co@NCNTs in step (4) of Example 1 was changed to 200 mg, and the other steps and the amounts of reactants were exactly the same as in Example 1, to obtain a graphene composite carbon nanotube-coated Co nanoparticle absorbing material, named Co@NCNTs / GO-3.
[0043] The samples prepared in the above examples were tested as follows:
[0044] 1. Material morphology observation
[0045] The morphology of the graphene composite carbon nanotube-coated Co nanoparticle absorbing materials obtained in Examples 1, 2 and 3 was observed using a scanning electron microscope and a transmission electron microscope. Figure 1 As shown, Figure 1 (a) is the SEM image of Example 1, Figure 1(b) is the SEM image of Example 2, Figure 1 (c) is the SEM image of Example 3, Figure 1 (d), 1(e) and 1(f) are TEM images of Example 2 at different viewing angles. Figure 1 (g), 1(h), 1(i) and 1(j) are Figure 1 (f) Corresponding C, N and Co element mapping spectra. Through the electron microscope, it can be seen that the particles prepared in this scheme have good morphology and surface state. The element mapping spectrum proves the corresponding relationship between the composition and structure of the corresponding materials, indicating that the present invention successfully synthesized the graphene composite carbon nanotube-coated Co nanoparticle absorbing material.
[0046] 2. Material XRD structure test
[0047] X-ray diffraction (XRD) was used to further characterize the structure of the graphene composite carbon nanotube-coated Co nanoparticle absorbing materials obtained in Examples 1, 2 and 3. It can be seen from the figure that there is a broadened peak at 2θ=26.5°, corresponding to the (002) crystal plane of graphitized C, and the peaks at 44.6°, 51.5° and 75.8° can respectively correspond to the (111), (200) and (220) crystal planes of Co (PDF#89-4307). We can also see from the XRD data that from Co@NCNTs / GO-1 to Co@NCNTs / GO-2 and then to Co@NCNTs / GO-3, the intensity of the Co diffraction peak gradually decreases. This is mainly because with the increase of GO content, it has a certain coating effect on Co nanoparticles, and the relative content of Co is also decreasing, so the diffraction peak intensity decreases. The XRD analysis results confirm that the present invention successfully synthesized the graphene composite carbon nanotube-coated Co nanoparticle absorbing material.
[0048] 3. Magnetization property test
[0049] The magnetic properties of absorbing materials containing magnetic particles play an important role in improving the impedance matching performance of absorbing materials. Therefore, the saturation magnetization intensity and coercive force of the material are usually determined by testing and drawing the hysteresis loop of the material to evaluate the magnetic properties of the absorbing material.
[0050] The static magnetic properties of the sample were tested and analyzed using a vibrating sample magnetometer. The results are as follows: Figure 3 As shown. Figure 3 (a) It can be seen that the saturation magnetization of the samples in Examples 1 to 3 are 101emu / g, 86.5emu / g and 82.3emu / g respectively. Figure 3(b) It can be seen that the coercive forces of the three samples are 123.2Oe, 133.2Oe and 124.13Oe respectively. The area within the hysteresis loop can quantitatively analyze the magnetic properties of the material. This test result shows that the graphene composite carbon nanotube-coated Co nanoparticle absorbing material prepared by the present invention has good magnetic properties.
[0051] 4. Impedance matching performance test
[0052] The impedance matching of materials is an important evaluation index for the ability of incident electromagnetic waves to enter the material. A good absorbing material must have good dielectric loss capacity and magnetic loss capacity, but the reverse is not necessarily true. This requires the material to have good impedance matching so that electromagnetic waves can enter the material as much as possible and be lost.
[0053] The electromagnetic parameters of the 1-18 GHz frequency band of the absorbing materials obtained in Examples 1, 2 and 3 were measured using the N5222A vector network analyzer of Agilent Corporation of the United States. The samples used were all in powder form, and the prepared absorbing materials were mixed with 70% paraffin wax, melted and mixed evenly, and then pressed into a coaxial ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm and a thickness of about 1-5 mm using a mold, and after cooling and taking out, placed in the coaxial fixture of the vector network analyzer for testing.
[0054] In the impedance matching diagram, the closer the value of Zin / Zo is to 1, the better the impedance matching performance of the material. Figure 4 (b) It can be seen that the impedance matching value of the sample in Example 2 has the largest area close to 1, indicating that its impedance matching performance is the best among the three materials, especially at 3.3 mm and 8.03 GHz, the impedance matching of the material is close to 1. Figure 4 (c) It can be seen that the impedance matching of the sample in Example 3 is second only to that in Example 2, and the impedance matching value is also relatively close to 1. Figure 4 (a) The area of the sample in Example 1 where the impedance matching value is close to 1 is relatively small. In summary, Example 2 has better impedance matching performance than Example 1 and Example 3, so it may also have better wave absorbing performance.
[0055] 5. Reflection loss experiment
[0056] The two-dimensional and three-dimensional reflection loss properties of the materials prepared in the embodiments of the present invention are as follows: Figure 5 As shown. Figure 5(c) and 5(d) show that Example 2 has the strongest reflection loss in the frequency band of 2 to 18 GHz. When the thickness is 3.3 mm, the maximum RL at 8.03 GHz is -71.17 dB, and the effective absorption bandwidth is 3.02 GHz, ranging from 6.74 to 9.76 GHz, which is consistent with the calculated impedance matching data. The reason why Example 2 has such a strong wave absorption performance is mainly because of the introduction of an appropriate proportion of graphene oxide, which has a good separation effect on Co@NCNTs. Co@NCNTs are relatively evenly attached to the surface of GO, forming more heterogeneous interfaces, greatly enhancing multiple interface polarization, and is also conducive to building a three-dimensional conductive network, resulting in good conduction loss. From Figure 5 It can be seen from Figures 5(e) and 5(f) that the reflection loss of Example 3 is smaller than that of Example 2. When the thickness is 3.2 mm, the maximum RL at 8.03 GHz is -28.07 dB, and the effective absorption bandwidth is 2.97 GHz, ranging from 6.81 to 9.68 GHz. The reflection loss value is lower than that of Example 3, which may be because too much GO is added and the GO sheets are agglomerated. Although it contributes to the real and imaginary parts of the dielectric loss, it will reduce the impedance matching ability of the material, and ultimately affect the absorbing performance of the material.
[0057] From the above data, it can be seen that when the thickness of the composite material prepared in Example 2 of the present invention is 3.3 mm, the maximum reflection loss at 8.03 GHz is as high as -71.17 dB, and the effective absorption bandwidth is 3.02 GHz, which reflects the optimal absorbing performance, indicating that the graphene composite carbon nanotube-coated Co nanoparticle absorbing material prepared by the present invention has good commercial application value.
[0058] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. Graphene composite carbon nanotube coated Co absorbing material, characterized in that: The method is obtained by cross-linking graphene with carbon nanotubes, wherein the carbon nanotubes are loaded with Co nanoparticles.
2. The graphene composite carbon nanotube-coated Co absorbing material according to claim 1, characterized in that: The X-ray crystal diffraction result of the wave absorbing material has a 2θ diffraction angle including a characteristic peak 2θ=26.5° of graphene, and characteristic peaks of 44.6°, 51.5° and 75.8° of Co nanoparticles.
3. The graphene composite carbon nanotube-coated Co absorbing material according to claim 1, characterized in that: The diameter distribution of the carbon nanotubes is 40-50 nm.
4. The graphene composite carbon nanotube-coated Co absorbing material according to claim 1, characterized in that: The particle size of Co nanoparticles is 40 to 50 nm.
5. The graphene composite carbon nanotube-coated Co absorbing material according to claim 1, characterized in that: The preparation method thereof comprises the following steps: S1, preparing a melamine precursor by a self-assembly method using melamine, cobalt salt and ethanol, and preparing carbon nanotubes coated with Co nanoparticles by calcining in an inert gas; S2. The carbon nanotubes coated with Co nanoparticles and graphene oxide are hydrothermally prepared into a graphene composite carbon nanotube-coated Co nanoparticle absorbing material.
6. The graphene composite carbon nanotube-coated Co absorbing material according to claim 5, characterized in that: In step S1, the cobalt salt is cobalt nitrate hexahydrate; the mass ratio of melamine, cobalt salt and ethanol is 1:1:20-25.
7. The graphene composite carbon nanotube-coated Co absorbing material according to claim 5, characterized in that: The graphene oxide is prepared by using NaNO3, KMnO4 and hydrogen peroxide.
8. The graphene composite carbon nanotube-coated Co absorbing material according to claim 5, characterized in that: In step S2, the mass ratio of carbon nanotubes covering Co nanoparticles to graphene oxide is 1:10-20.
9. The graphene composite carbon nanotube-coated Co absorbing material according to claim 5, characterized in that: In step S2, the hydrothermal method temperature is 100-120°C, and the reaction time is 1-3 hours.
10. Use of the graphene composite carbon nanotube-coated Co absorbing material according to any one of claims 1 to 9 in the field of electromagnetic wave absorption.